PENYUSUNAN HARGA POKOK PRODUK SEBAGAI DASAR PENETAPAN HARGA JUAL BARANG BEKAS BERNILAI EKONOMIS DILAKSANAKAN DI PANTI JOMPO PPSLU SUDAGARAN KABUPATEN BANYUMAS (Universitas Wijayakusuma Purwokerto, 2024)
Community Service is one of the tridhrama activities of Higher Education., we equip the residents of the PPSLU Sudagaran nursing home, Banyumas Regency, to utilize their time by utilizing waste materials into products of economic value. So that this activity can improve welfare, it is necessary to determine the selling price of the product so that it can compete in the market. The method of community service is through knowledge transfer and mentoring. The result of community service is increasing the knowledge of the residents of the PPSLU Sudagaran Banyumas Regency nursing home in making economically valuable products and being able to determine the right selling price so that the product can compete in the market, thereby increasing welfare.